Biological augmentation to promote meniscus repair: from basic science to clinic application—state of the art. Issue 3 (16th March 2020) - Carlson Strother, Courtney R; Saris, Daniel B F; Verdonk, Peter; Nakamura, Norimasa; Krych, Aaron J
Abstract : Meniscus tears range from acute tears during physical activity to chronic degenerative tears. The role of the meniscus in knee stability, load distribution, knee proprioception and arthritis prevention has been well established, and successful repair of meniscus tears has better clinical outcomes and protection from increased degenerative changes. Advancements in surgical techniques have demonstrated meniscus repair is possible in tears previously deemed unsalvageable. In addition, the use of biological augmentation has improved rates of meniscal healing, and the use of biologics is an active area of investigation. In this article, we review current methods of biological augmentation to promote meniscus healing, including biological injections, concomitant procedures and biological membranes.